PENINGKATAN PERPINDAHAN PANAS PADA FAN COIL UNIT (FCU) DENGAN NANOPARTI Al2O3 - Daud S. Anakottapary; I N Sutarna; Putu Wijaya Sunu; I Made Rasta (JURNAL INTEGRASI, 2019)
Experimental studies on Fan Coil Unit (FCU) were conducted to investigate heat transfer characteristics due to the addition of Al2O3 nanoparticles. The aims of this study was to reveal the phenomenon of nanofluid particle influences on heat transfer performance indicators. This investigation used tube and fin FCU type with cold fluid is water-Al2O3 nanofluid and hot fluid is ambient air. The cold fluid volume flow rate is 15 lpm and the hot fluid mass flow rate is 0.48 kg/s. The concentration of nanoparticles was 0.1%. The ambient air temperature inlet of FCU is 28 ± 0,50C while the cold fluid temperature entering the FCU is 19 ± 0,50C. In this study the performance parameters on cold fluid with nanoparticles were compared with no nanoparticles. The results showed that the small addition of nanoparticles in cold fluid increased heat transfer in FCU by 9.2%.